Additional growth substances on spring wheat under conditions of moisture deficiency - Timofeev Vyacheslav Nikolaevich (BIO Web of Conferences)
The research was carried out in the conditions of the Northern forest-steppe of the Tyumen region, with weather indicators in 2023, characterized by elevated temperatures and lack of moisture. The tested products: biogenic FeCo, humic preparation, nanopreparation containing potassium, biogor, bacterial preparation, chemical fungicide had different effects on the morphological parameters of the plant. The development of embryonic organs such as root mass exceeded other options by 0.7 - 1.8 g when using a chemical disinfectant and Biogor Zh. High germination rate of 96% was observed when processing Biogor Zh seeds in a mixture with a bacterial consortium, which is higher than other options by 2-4%. Reduction in sprout length by 1.0 cm relative to absolute control for most options. The options used had no effect on seed diseases and root rot, with the exception of a fungicidal disinfectant with an effectiveness of 93-100%. The growth of the top leaf in the tillering phase - the tubes exceeded by 3-4 cm according to the Biogor-Zh option when treating seeds and plants in the tillering phase. The development of the flag leaf also exceeded when Biogor Zh was used in combination with bacteria, biogenic iron in its pure form and with a humic preparation applied in the tillering phase. Plant biometric indicators such as the weight of stems by 3-6 g, leaves, ears by 1.0-1.7 g exceeded the control and other options when using humic preparations and their mixtures with biogenic iron.